Reliability and age of information analysis of 5G IoT for intelligent communication. (July 2022) - Chandra, Saurabh; Prateek,; Arya, Rajeev; Verma, Ajit Kumar
Highlights: Outage probability and fairness-based power control scheme has been proposed to enhance throughput for 5G-IoT networks. Analysis and minimization of age of information (AoI) related to outage probability to achieve system reliability. Minimization of outage probability to achieve low power consumption even during high utilization of resources of 5G-IoT network in D2D communication. Formulation of fairness index based outage probability & age of information algorithm (abbreviated as FOPA Algorithm) for comparison with benchmark techniques. Abstract: Device-to-Device (D2D) communication in fifth generation (5G)-Internet of Things (IoT) Networks suffer from high-power outage and interference with cellular spectrum. To address these issues, a problem is formulated to minimize the outage power for the maximization of throughput. We investigate Outage Probability (OP) and Age of Information (AoI) to propose fairness-based power control (FOPA) technique. In the first stage, throughput gets maximized by minimizing the outage power. Since a lower value of AoI is a desirable trait, it should be minimized with the help of OP in the second stage. Results confirm that the proposed FOPA technique improves performance by 14.28% and 20% in terms of throughput and spectrum efficiency, respectively. AoI is minimized by 16%-38% compared to the benchmark schemes. System reliability exhibits a low variance of 0.0856, 0.0429 and 0.0383. The proposed work may be used in spectrally efficient IoT devices and scalable communication systems beyond 5G. Graphical abstract: Image, graphical abstract